Humoral immunity against SARS-CoV-2 evoked by heterologous vaccination groups using the CoronaVac (Sinovac) and BNT162b2 (Pfizer/BioNTech) vaccines in Chile - Díaz-Dinamarca, Diego A.; Díaz, Pablo; Barra, Gisselle; Puentes, Rodrigo; Arata, Loredana; Grossolli, Jonnathan; Riveros-Rodriguez, Boris; Ardiles, Luis; Santelises, Julio; Vasquez-Saez, Valeria; Escobar, Daniel F.; Soto, Daniel; et al. (Frontiers in Public Health, 2023)
Severe acute respiratory syndrome virus 2 (SARS-CoV-2) has caused over 7 million deaths worldwide, with more than 61,000 deaths in Chile. The Chilean government has implemented a vaccination program against SARS-CoV-2, with over 17.7 million people receiving a complete vaccination scheme. The final target is 18 million individuals. The most common vaccines used in Chile are CoronaVac (Sinovac) and BNT162b2 (Pfizer-Biotech). Given the global need for vaccine boosters to combat the impact of emerging virus variants, studying the immune response to SARS-CoV-2 is crucial. In this study, we characterize the humoral immune response in inoculated volunteers from Chile who received vaccination schemes consisting of two doses of CoronaVac [CoronaVac (2×)], two doses of CoronaVac plus one dose of BNT162b2 [CoronaVac(2×) + BNT162b2 (1×)], and three doses of BNT162b2 [BNT162b2 (3×)]. We recruited 469 participants from Clínica Dávila in Santiago and the Health Center Víctor Manuel Fernández in the city of Concepción, Chile. Additionally, we included participants who had recovered from COVID-19 but were not vaccinated (RCN). We analyzed antibodies, including anti-N, anti-S1-RBD, and neutralizing antibodies against SARS-CoV-2. We found that antibodies against the SARS-CoV-2 nucleoprotein were significantly higher in the CoronaVac (2×) and RCN groups compared to the CoronaVac (2×) + BNT162b2 (1×) or BNT162b2 (3×) groups. However, the CoronaVac (2×) + BNT162b2 (1×) and BNT162b2 (3×) groups exhibited a higher concentration of S1-RBD antibodies than the CoronaVac (2×) group and RCN group. There were no significant differences in S1-RBD antibody titers between the CoronaVac (2×) + BNT162b2 (1×) and BNT162b2 (3×) groups. Finally, the group immunized with BNT162b2 (3×) had higher levels of neutralizing antibodies compared to the RCN group, as well as the CoronaVac (2×) and CoronaVac (2×) + BNT162b2 (1×) groups. These findings suggest that vaccination induces the secretion of antibodies against SARS-CoV-2, and a booster dose of BNT162b2 is necessary to generate a protective immune response. In the current state of the pandemic, these data support the Ministry of Health of the Government of Chile’s decision to promote heterologous vaccination, as they indicate that a significant portion of the Chilean population has neutralizing antibodies against SARS-CoV-2.